Caracterização de mutações da osteogênese imperfeita em pacientes do Espírito Santo : estudo dos genes IFITM5, COL1A1 e COL1A2 - Silva, Dalila Avila (2018)
Osteogenesis imperfecta (OI) is a disease that occurs due to the generalized disorder of the connective tissue causing mainly bone fragility. This disorder is most often caused by mutations in the genes producing collagen type I chains, COL1A1 or COL1A2, although mutations in new genes involved in the pathway of bone metabolism have been constantly discovered. There are currently 17 genes related to this disease. One of them is the IFITM5 gene, still little featured in most populations. Because it has several OI-causing genes, the Next Generation Sequencing (NGS) methodology, a large-scale sequencing strategy, has been widely used. However, the mutations identified by NGS need to be validated to give reliability to the results. Thus, the objective of this work was to identify mutations in the IFITM5 gene and validate mutations identified by NGS in the genes COL1A1 and COL1A2 to characterize the pattern of mutations in these genes in patients from Espírito Santo. This study had an initial sample of 31 patients who were previously analyzed for other genes. From this sample, 8 individuals who presented inconclusive molecular results were studied for the IFITM5 gene. The presence of the c. -14C> T mutation was detected in one patient. This mutation occurs in the 5'-UTR region of the gene and is recurrent in several populations of the world. The validation of mutations was performed in 16 individuals who presented genetic alterations in the COL1A1 or COL1A2 genes detected by NGS. Only one of the sequences identified by NGS has not been validated. This study confirmed that mutations in the COL1A1 and COL1A2 genes are found in approximately 75% of patients, whereas in the IFITM5 gene mutations are found in approximately 3% of patients with OI of Espírito Santo. These results may help in the development of more efficient molecular diagnostic strategies for this disease.